Exploring intersectional determinants of, and interventions for, low uptake of human papillomavirus vaccine in sub-Saharan Africa: a scoping review protocol - Peter Ntoiti Kailemia; Victoria Mukami (BMJ Open)
Introduction Cervical cancer is the most diagnosed cancer and the leading cause of cancer-related death in 36 low- and middle-income countries, with the majority located in sub-Saharan Africa (SSA), South America and Southeastern Asia. The highest regional incidence and mortality occur in SSA. Despite the high efficacy and cost-effectiveness of the human papillomavirus (HPV) vaccine in preventing cervical cancer, its uptake remains unacceptably low in SSA. This scoping review aims to integrate evidence from SSA on social determinants of HPV vaccine uptake with complementary evidence on interventions to promote its uptake.Methods and analysis The proposed review will be conducted following the guidelines of the Joanna Briggs Institute Scoping Review Methodology Group. Additionally, a sequential explanatory design will guide the integration of determinant evidence with intervention evidence. This scoping review will be reported per the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Extension for Scoping Reviews checklist. Six databases, PubMed/MEDLINE, LIVIVO, Google Scholar, BASE (Grey Literature), preprint databases (eg, OSF and medRxiv) and African Journals Online will be searched, with results limited to English language publications and those published from 2006 to 2024. Two forms will be used for data extraction from determinant and intervention studies by two independent reviewers. A narrative summary of evidence from both determinant and intervention studies will be conducted. Furthermore, a multilevel analysis will be conducted to explore the intersections of determinants across socioecological levels of health behaviour. A further integrative cross-study analysis of results from determinant and intervention studies will be conducted, where the determinant evidence will be used to interrogate the intervention evidence. Data will be presented in tables and matrices.Ethics and dissemination No ethical approval will be required for this study because it will be based on data collected from publicly available records. The review results will be disseminated widely through a peer-reviewed publication and other forums such as workshops, conferences and meetings with local health administrators, policymakers and other wider stakeholder engagements.